Pemilihan Siswa Praktek Kerja Industri Berbasis Komputer Terbaik Menggunakan Metode AHP - Alkodri, Ari Amir; Fitriyani, F; Anisah, A (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
Prakerin is a guidance, training and learning activity for vocational school (Vocational High School) students carried out in the business world or industrial world which is related to student competencies according to the student's field of work. In general, schools implement vocational vocational internship programs to improve students' skills in their fields. This program is implemented to prepare students to work in the field and also be able to practice the theory they have learned at school. That way, when they graduate, students can adapt more quickly to the world of work in the ISB Atma Luhur computer laboratory. The problem is that the special laboratory assistant, Head of the Computer Laboratory, has difficulty assessing the comparison of some internship students with other internship students to determine whether their performance is the best or not. The calculation of the final score uses the average value method (mean) so that all criteria are considered to have the same weight in terms of importance so that it is not possible to know which criteria are more important. The aim of the research is to apply the AHP method to select the best Industrial Work Practices, therefore it is obtained to determine the criteria weights and student rankings for the best Industrial Work Practices so that they can be used as a basis for decision making and applied by the Head of the Computer Laboratory in selecting the best Industrial Work Practices.